Penggunaan Aplikasi Digital untuk Mendukung Kegiatan Organisasi Siswa SD Negeri 1 Bente - Abubakar; Alif Ramadhan; Sulfan (PT Bukuloka Literasi Bangsa, 2026)
The development of digital technology has had a major impact on education, including the management of student organization activities in elementary schools. This study aims to determine the use of digital applications in supporting student organization activities at SD Negeri 1 Bente and to identify the benefits and obstacles faced in their implementation. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results showed that the use of digital applications such as WhatsApp, Google Meet, Canva, and Google Forms helped improve communication, coordination, information dissemination, and the efficiency of student organization activities. In addition, the use of digital applications also increased students' creativity and participation in school activities. However, there are still several obstacles such as limited internet access, differences in technological skills, and limited digital devices. Therefore, support from schools and parents is needed to improve the effectiveness of using digital applications in student organization activities. Keywords: digital applications, student organizations, educational technology, elementary school